ANALYSIS OF REJECTION OF APPLICATION FOR MARRIAGE ISBAT AND ORIGIN OF CHILDREN - Nurhalimah Nurhalimah (Jurnal Multidisiplin Sahombu, 2021)
Isbat marriage is a process of ratifying the marriage of a married couple who previously had a sirri marriage. The purpose of marriage isbat is to obtain a marriage certificate as proof of the validity of the marriage in accordance with the legislation in force in Indonesia. As stipulated in Law No. 1 of 1974 concerning Marriage, article 2 paragraph (2) and the implementation of marriage isbat is only intended for certain matters as in Article 7 paragraph (1), (2), (3) KHI. In the determination of the Blora Religious Court, it was found that there was a determination of the application for isbat marriage for sirri marriages which was accumulated with the determination of the origin of the child register Number: 0056/Pdt.P/2015/Pa.Bla. Panel of Judges at the Blora Religious Court. did not grant all requests. In the determination, a husband and wife want to ratify their sirri marriage and determine the child from the marriage as their legal child. number: 0056/Pdt.P/2015/PA.Bla?. What are the legal consequences for the determination of the case related to the protection of children's civil rights? This type of research is juridical-empirical research. The primary data used is the case file of the Blora Religious Court Number: 0056/Pdt.P/2015/Pa.Bla. and an interview with the Judge who decided the case Number: 0056/Pdt.P/2015/PA.Bla. Data collection techniques are interviews and documentation. while the analysis technique uses descriptive-analysis. The results showed that 1). the determination of the Blora Religious Court Number: 0056/Pdt.P/2015/PA.Bla in the case of the application for marriage isbat and the origin of the child is still not able to provide justice and benefits for the justice-seeking community. That is not being able to provide protection, especially to the child, even though the child was born as a result of a legal sirri marriage, it's just that according to state law the conditions and pillars are not fulfilled, because the woman is "still being someone else's wife" but has been divorced verbally and legally. abandoned for more than 3 years. This kind of prohibition or condition is actually a temporary prohibition, therefore the Panel of Judges should review the marriage ban. So in this case, it would be better if the Panel of Judges did not only look at the procedural law which only concerned with the formality aspect, but the Panel of Judges also looked at the case from the fiqh perspective. 2) While the legal consequences for the determination of the Blora Religious Court Number: 0056/Pdt.P/2015/PA.Bla against the rejection of the application for marriage isbat and the origin of the child, namely the child born as a result of the sirri marriage does not have civil rights from the father the biology. even though the child born from the legal marriage Bla against the rejection of the application for isbat marriage and the origin of the child, namely the child born as a result of the sirri marriage does not have civil rights from his biological father. even though the child born from the legal marriage Bla against the rejection of the application for isbat marriage and the origin of the child, namely the child born as a result of the sirri marriage does not have civil rights from his biological father. even though the child born from the legal marriage